Analisis Struktur Biaya UMKM (Studi Kasus Pada UMKM Quuen Bakery) - Aryan Ari Sepri YH; Mila Aulia (Prodi Agribisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia’s economy; however, limitations in cost management often hinder efficiency and competitiveness. This study aims to analyze the production cost structure of Queen Bakery MSME located in Bumi Agung Village, Kalianda District. The research employed a descriptive qualitative approach using a case study method. Primary data were collected through observation and interviews, supported by secondary data. Cost structure analysis was conducted by classifying production costs into fixed costs and variable costs, followed by the calculation of Total Cost (TC), Average Total Cost (ATC), Average Variable Cost (AVC), and Average Fixed Cost (AFC). The results show that with a production volume of 3,000 bread units per month, the total production cost amounted to IDR 13,100,000, consisting of fixed costs of IDR 3,900,000 (29.77%) and variable costs of IDR 9,200,000 (70.23%). The calculated ATC was IDR 4,367 per unit, AVC was IDR 3,067 per unit, and AFC was IDR 1,300 per unit. The cost structure of Queen Bakery MSME is dominated by variable costs, particularly raw material expenses. These findings indicate that increasing production volume has the potential to reduce AFC and ATC, thereby improving cost efficiency and business competitiveness. The results of this study are expected to serve as a reference for cost management and pricing decisions in bakery MSMEs.